Improvement of the scattering center extraction by using the modified approximate prolate series interpolants - Bolukbas, Deniz; Ergin, A. Arif (John Wiley & Sons Inc, 2007)
The three-dimensional (3D) scattering center model of a complex target can be obtained from the 3D inverse synthetic aperture (ISAR) image by using the CLEAN algorithm. To form the ISAR image from the results of a shooting-and-bouncing- ray (SBR) analysis, the image is updated on a ray-by-ray basis using a ray-spread function, which turns out to be a '' sine '' function. The '' sine '' function does not decay rapidly, yielding a harsh trade-off: in case the full '' sine '' function is used, the algorithm becomes computationally intense. On the other hand, if it is truncated, convergence problems arise. To solve this tradeoff problem, the use of a band-limited interpolant function, namely, modified approximate prolate series (MAPS) is proposed instead of the '' sine '' function. The suggested MAPS can be shown to have better truncation error bounds than other ray spread functions. By using the suggested MAPS functions, the sidelobe artifacts are minimized and the computational complexity is decreased while extracting the scattering centers with correct positions, amplitudes, and better resolution. (C) 2007 Wiley Periodicals, Inc.
Keywords: ISAR image; band-limited interpolation; CLEAN algorithm; ray-spread function; approximate prolate spheroid series